2001
DOI: 10.1074/jbc.m010104200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Native Cation Channel Activated by Ca2+ Store Depletion in Vascular Smooth Muscle Cells

Abstract: Depletion of intracellular Ca2؉ stores activates capacitative Ca 2؉ influx in smooth muscle cells, but the native storeoperated channels that mediate such influx remain unidentified. Recently we demonstrated that calcium influx factor produced by yeast and human platelets with depleted Ca 2؉ stores activates small conductance cation channels in excised membrane patches from vascular smooth muscle cells (SMC). Here we characterize these channels in intact cells and present evidence that they belong to the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 51 publications
5
127
1
1
Order By: Relevance
“…A clear alternative is the suggested diffusible messenger for CCE, termed calcium inf lux factor (9,10). Interestingly, there is recent evidence for such a mode of signaling in vascular smooth muscle cells (48), which is one of the cell types that expresses the nonselective cation channel version of CCE (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear alternative is the suggested diffusible messenger for CCE, termed calcium inf lux factor (9,10). Interestingly, there is recent evidence for such a mode of signaling in vascular smooth muscle cells (48), which is one of the cell types that expresses the nonselective cation channel version of CCE (18).…”
Section: Discussionmentioning
confidence: 99%
“…In other cell types, currents have been observed that have moderate divalent cation selectivity (12,13), and there are a number of examples of store-operated, nonselective cation currents (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Cells-Primary culture SMC from mouse (mSMC) and rabbit (rSMC) aorta were prepared as described previously (10,25). Human platelets were prepared from the platelet-rich plasma as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…9). Second, nonselective SOC channels of small, but resolvable 3 pS conductance has been found and described on single channel and whole-cell current levels by us (10,11) and by others (12)(13)(14)(15)(16)(17)(18) in vascular SMC and human platelets. Despite a great physiological importance of both types of SOC channels, the molecular mechanism of their activation is still unresolved.…”
Section: ؉mentioning
confidence: 99%
“…As such, the current finding that an ,25 pS channel underlies CPA-and BAPTA-AM-evoked NSCC currents in bovine TSMs is novel. The magnitude of the conductance described herein is 10-fold greater than that reported for store depletion-activated NSCCs in vascular smooth muscle cells [25,30,31]; the possibility that small conductance NSCCs were hidden within the noise inherent in the recordings cannot be ruled out. Involvement of this NSCC explains why the Ca 2+ entry induced by CPA was resistant to nifedipine ( fig.…”
Section: Discussionmentioning
confidence: 60%